Determinants of capital structure based on pecking order theory in Malaysian market / Husna ‘Atiah Salleh - Salleh, Husna ‘Atiah (2014)
The main objective of this study is to investigate the determinants of capital structure based on pecking order theory in Malaysian stock market that listed in the Bursa Malaysia. The scope of the study covers from seven year period which is from 2005 to 2011. The data is derived from Datastream which consists of 138 companies with number of observation totaling 758. This study employs the debt to equity as dependent variable while, the independent variables are asset structure, profitability, growth opportunities, liquidity, firm size and dividend. Based on the empirical result, shows that the asset structure, profitability, growth opportunities, liquidity and dividend is significantly related to capital structure. However, the study finds firms size insignificant towards capital structure. In short, the study suggests that pecking order theory is one of best theory in explaining capital structure policy in Malaysian stock market